Virgil, Aeneid 7 : a commentary - Virgil. (Mnemosyne, Supplements, 2000)
This commentary was begun in 1967, but most of the period from 1971 to 1996 was spent on work that was in some sense an essential preliminary to a detailed study of Aeneid 7. The work will serve as a guide to recent (and future) work on Virgilian language, grammar, syntax and style. Recent approaches to the text have been, where possible, taken into account, with sympathy but without jargon. Virgil's sources, in verse and prose, have been studied with special care and the commentary presents a coherent approach to Virgil's view of Italian religion, antiquities and topography. Unusually full indexing is intended to further the book's use as a guide to many aspects of Augustan poetic idiom. There is a text independent of recent editions and a precise, prose translation.